Peranan Al-Mudharabah Sebagai Salah Satu Produk Perbankan Syariah Dalam Upaya Mengentaskan Kemiskinan Di Indonesia - Dwi Agung Nugroho Arianto (Jurnal Ekonomi dan Pendidikan, 2011)
One of the fight against poverty can be done by expanding access to Micro, Small and Medium Enterprises (UMKM) in obtaining such capital facilities through Islamic banking. Based on the basic principle of its products, Islamic banks have the financing to the principle of profit sharing, which developed the product mudharabah. This financing is productive because the capital invested for the supply of labor so as to empower the economy through small community of Micro, Small and Medium Enterprises (UMKM). By developing micro, small and medium enterprises it will help create jobs and economic growth in the real sector, thus keeping down unemployment and poverty in Indonesia.